1967
DOI: 10.1083/jcb.34.1.311
|View full text |Cite
|
Sign up to set email alerts
|

THE TRANSFORMATION OF THE PLASMODIUM GALLINACEUM OOCYST IN AEDES AEGYPTI MOSQUITOES

Abstract: Sporoblast and sporozoite formation from oocysts of the avian malarial parasite, Plasmodium gallinaceum, after the seventh day of infection in Aedes aegypti mosquitoes offers an interesting example of differentiation involving the appearance and modification of several cellular components. Sporoblast formation is preceded by (a) invaginations of the oocyst capsule into the oocyst cytoplasm, (b) subcapsular vacuolization and cleft formation, (c) the appearance of small tufts of capsule material on the previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

1969
1969
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…For P. berghei, cristae have been reported for pre-erythrocytic stages (50), gametocytes, sporogonic stages (51), and oocysts (52,53), whereas trophozoites were termed acristate (51). Similarly, few cristae were found in asexual stages of P. falciparum and more in gametocytes (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…For P. berghei, cristae have been reported for pre-erythrocytic stages (50), gametocytes, sporogonic stages (51), and oocysts (52,53), whereas trophozoites were termed acristate (51). Similarly, few cristae were found in asexual stages of P. falciparum and more in gametocytes (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Plaquelike differentiations within the nuclear envelope resembling those of the Ascomycetes have been described in some protozoa such as the malarial parasites (Aikawa et al, 1967;Terzakis et al, 1967;Aikawa and Beaudoin, 1968;Scalzi and Bahr, 1968), hypermastigid flagellates (Hollande and Valentin, 1968), and radiolarians (Hollande et al, 1969). Some authors have suggested that such polar plaques might represent a specialized pore complex (Robinow and Marak, 1966;Scalzi and Bahr, 1968;Unger et al, 1971;Peters on et al, 1972.…”
mentioning
confidence: 99%
“…Early light microscope studies on the development of Plasmodium oocysts have indicated a similar location in the midgut of the mosquito vector (12). In their recent ultrastructural studies of oocyst transformation in P. gallinacezm and P. cynomolgi, Terzakis et al (18,19,20) have suggested that the oocysts come to lie on "the external surface of the epithelial basal lamina." This indicates that the ookinete must penetrate through the basal lamina before transforming into an oocyst.…”
Section: Discussionmentioning
confidence: 97%
“…When ookinetes of Leucocytozoon round up beneath the basal lamina of the midgut epithelium to form oocysts, they undergo no further growth, and in most species less than 100 sporozoites are formed around a single sporoblast center (7). Oocysts of Plasmodium, on the other hand, may undergo a 5000-fold increase in volume during their development, and thousands of sporozoites are formed around multiple sporoblast centers (13,18,19,20,22). The latter are produced by subcapsular vacuolization and cleft formation, processes which were not observed during the development of the smaller oocysts of L. simondi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation